Durability Performance of Geopolymer Concrete of Various Strength - Meechang, Clarence Meripa; Muthuramalingam, Jayakumar; Tam, Nicholas (Civil and Sustainable Urban Engineering, 2023)
Geopolymers, primarily composed of fly ash, have proved an excellent substitute for ordinary portland cement (OPC) in terms of sustainability and productivity. In order to determine the geopolymer concrete's (GPC) resistance to chemical assaults and water permeability, it is necessary to obtain geopolymer concrete (GPC) of varying strengths after normal curing. The objectives of the research was to test the durability performances of the GPC of various strength under normal curing and investigating the optimum strength based on durability testing of the GPC. For this research, different type of cement-to-fly ash ratio was used for various strength data. The appropriate mixture was conducted by using the trial mix method in order to obtain better accuracy of the results data during the mixing design process. To satisfy the varied strength designs, a small proportion of OPC is added to the GPC mixture as part of the mix design. After 28 days of curing, this durability testing is undertaken after the concrete has reached its maximum strength. The compressive strength test and weights were performed and compared to the GPC mix design at 60 °C after heat curing. The 8% OPC replacement has greater resistance to sulfate attack, saltwater exposure, and water permeability compared to the 6% and 7% OPC alternatives. Consequently, the experiment reveals that the GPC's durability and strength increase as the percentage of OPC increases.